Software-Defined Networking (SDN) with OpenStack : leverage the best SDN technologies for your OpenStack-based cloud infrastructure /: leverage the best SDN technologies for your OpenStack-based cloud infrastructure. (2016) - Subramanian, Sriram; Voruganti, Sreenivas
No abstract available